Sustainable recycling of metal machining swarf via spark plasma sintering - Sutherland, Alexandra E., author; Ma, Kaka, advisor; Sambur, Justin, committee member; Simske, Steve, committee member (Colorado State University. Libraries, 2021)
In general, extracting virgin metals from natural resources exerts a significant environmental and economic impact on our earth and society. Production of virgin stainless steels and titanium (Ti) alloys have particularly caused concerns because of the high demands of these two classes of metals across many industries, with low fractions of scraps (less than one-third for steels and one-fourth for Ti alloys) that are currently recirculated back into supply. In addition, the conventional recycling methods for metals require multiple steps and significant energy consumption. With the overarching goal of reducing energy consumption and streamlining recycling practices, the present research investigated the effectiveness of direct reuse of stainless steel swarf and Ti6Al-4V alloy swarf as feedstock for spark plasma sintering (SPS) to make solid bulk samples. The parts made from machining swarf were characterized to tackle material challenges associated with the metal swarf such as irregular shapes and a higher amount of oxygen content. The hypothesis was that while solid bulk parts made from metal swarf would contain undesired pores that degrade mechanical performance, some mechanical properties (e.g., hardness) can be comparable or even outperform the industrial standard counterparts made from virgin materials, because of cold working and grain refinement that occurred to the swarf during machining and the capability of SPS to retain ultrafine microstructures. 304L stainless steel and Ti-6Al-4V (Ti64) alloy swarf were collected directly from machining processes, cleaned, and then consolidated to bulk samples by SPS with or without addition of gas atomized powder. Nanoindentation and Vickers indentation were utilized to evaluate the hardness at two length scales. Ball milling was performed on Ti64 to assess the energy consumption required to effectively convert swarf to varied morphologies. In addition, to provide insight into the macroscale mechanical behavior of the materials made by SPS of recycled swarf, finite element modeling (FEM) was used to predict tensile stress-strain curves and the corresponding stress distributions in the samples. The key findings from my research proved that reuse of austenitic stainless steel chips and Ti64 alloy swarf as feedstock for SPS is an effective and energy efficient approach to recycle metal scraps, compared to the production and use of virgin gas atomized powders, or conventional metal recycling routes. The mechanical performance of the samples made from metal swarf outperformed the relevant industrial standard materials in terms of hardness while the ductility remains a concern due to the presence of pores. Therefore, future work is proposed to continue to address the challenges associated with mechanical performance, including but not limited to, tuning the SPS processing parameters, quantifying an appropriate amount of addition of powder as a sintering aid, and refining the morphology of the swarf by ball milling. It is critical for the health of our planet to always consider the tradeoff between energy consumption and materials performance.
Keywords: metal; spark plasma sinter; titanium; recycling; energy; stainless steel